1993
DOI: 10.1111/j.1559-1816.1993.tb01098.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sentencing Decisions: The Beliefs, Personality Variables, and Demographic Factors of Juvenile Justice

Abstract: The role of beliefs, personality variables, and demographic factors in the sentencing of juvenile offenders was investigated. The subjects (1,030 members of the juvenile justice system) judged hypothetical juvenile perpetrators. Various personality, belief, and demographic variables were found to be related to sentencing severity; these relationships differed based on the type of crime judged. Further, relations among these variables and sentencing behavior indicated three coherent patterns or resonances. A li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…Although this research has had important implications for understanding and influencing public opinion, the research has been criticized for mis-measuring punitiveness by equating it with retributivism (Templeton and Hartnagel 2008) and there have been some inconsistent findings where punitiveness appears to be related to social or deterministic explanations for offending rather than dispositional ones (e.g., Davis et al 1993;Lieber and Woodrick 1997;Viney et al 1982). Strossner and Green (1990) have criticized this research for grouping together different types of determinism (e.g., psychological determinists versus religious-philosophical determinists) in their measurements.…”
Section: Beyond Locus Of Control: the Redeemability Hypothesismentioning
confidence: 97%
See 1 more Smart Citation
“…Although this research has had important implications for understanding and influencing public opinion, the research has been criticized for mis-measuring punitiveness by equating it with retributivism (Templeton and Hartnagel 2008) and there have been some inconsistent findings where punitiveness appears to be related to social or deterministic explanations for offending rather than dispositional ones (e.g., Davis et al 1993;Lieber and Woodrick 1997;Viney et al 1982). Strossner and Green (1990) have criticized this research for grouping together different types of determinism (e.g., psychological determinists versus religious-philosophical determinists) in their measurements.…”
Section: Beyond Locus Of Control: the Redeemability Hypothesismentioning
confidence: 97%
“…In particular, a considerable body of research has drawn upon attribution theory, linking public opinion to individualistic as opposed to situational attributions (Carroll and Payne 1977;Carroll et al 1987;Cullen et al 1985;Davis et al 1993;Graham et al 1997;Grasmick and McGill 1994;Hawkins 1981;Hogarth 1971;Lurigio et al 1994;Maruna and King 2004;Nettler 1959;Shaver 1975;Stinchcombe et al 1980;Young 1991). The dependant variable in these studies varies from penal goals (e.g., support for rehabilitation or retribution) (Templeton and Hartnagel 2008), to support for the death penalty (e.g., Young 1991), to attitudes toward parolees (Demski and McGlynn 1999), to reactions to the O. J. Simpson trial (Graham et al 1997).…”
Section: Accounting For Punitivenessmentioning
confidence: 99%
“…Laws are based on the shared assumptions that ordinary people hold about how people act and how their actions can be controlled. In this way, public feeling about the causes of offending behaviour affects what they think ought to be done about crime (Davis, Severy, Kraus, & Whitaker, 1993;Flanagan, 1996: Lilly, Cullen, & Ball, 1989Roberts. 1992).…”
mentioning
confidence: 99%
“…This negative perspective on youth psychiatry and collaboration with youth psychiatrists may influence judges' decisions to refer a minor to mental health services. Previous research has indicated that the attitudes of the juvenile judge influence the decision regarding referral (D'Angelo, 2007;Davis, Severy, Kraus, & Withaker, 1993). Conversely, Breda (2001) found that a positive mental health orientation did not result in more referrals to mental health services.…”
Section: The Role Of the Youth Psychiatristmentioning
confidence: 79%